Porn-cultural Industries: female children and teenagers’ eroticisation - Antonia Cava (Culture e Studi del Sociale)
The communicative landscape is filled with representations of women filtered by a male gaze, in which space is given mainly to standardised female images, precisely sharing a central role in the body dimension. This paper examines the portrayal of women's bodies within cultural industries, focusing on the profound impact of these images on the socialization of gender and sexuality in young girls. It analyses how the hypersexualized media landscape, particularly images that are sexualizing children, affects self-perception and can contribute to serious social issues, including the proliferation of child pornography facilitated by digital technologies. The paper investigates the entrenchment of stereotypical gender images, leading to self-objectification and adult-like sexual self-presentation in female children, often pressuring them to meet restrictive beauty standards. Furthermore, the research underscores the limited scholarship – particularly within Italian contexts – on how media-driven sexualization connects to the sexual exploitation of minors. Emphasizing the urgency of counter-narratives, this paper advocates for balanced media representations that encourage positive gender and body image socialization, fostering spaces free from objectification for children and teenagers.